2014
DOI: 10.2214/ajr.12.10518
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sonazoid (Perflubutane) for Contrast-Enhanced Ultrasound in the Differentiation of Focal Breast Lesions: Phase 3 Multicenter Clinical Trial

Abstract: CEUS using Sonazoid was confirmed to be superior to unenhanced ultrasound for the differential diagnosis (benign vs malignant) of focal breast lesions in terms of diagnostic accuracy with no serious adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 30 publications
1
51
1
Order By: Relevance
“…Sonazoid ® microbubbles were shown to improve the accuracy of diagnosis of prostate cancer, which could reduce the number of biopsies patients need to receive to achieve a similar diagnostic result 31 . In Japan, Sonazoid ® was also used in a phase III clinical trial to compare its diagnostic potential of focal breast lesions against unenhanced ultrasound and contrast enhanced MRI (Figure 2) 32 . The study found that while CEUS technology did not statistically significantly increase the sensitivity of the diagnosis, it substantially enhanced the accuracy and specificity at a reduced cost 32 .…”
Section: Clinical Applications Of Ultrasound Contrast Agentsmentioning
confidence: 99%
“…Sonazoid ® microbubbles were shown to improve the accuracy of diagnosis of prostate cancer, which could reduce the number of biopsies patients need to receive to achieve a similar diagnostic result 31 . In Japan, Sonazoid ® was also used in a phase III clinical trial to compare its diagnostic potential of focal breast lesions against unenhanced ultrasound and contrast enhanced MRI (Figure 2) 32 . The study found that while CEUS technology did not statistically significantly increase the sensitivity of the diagnosis, it substantially enhanced the accuracy and specificity at a reduced cost 32 .…”
Section: Clinical Applications Of Ultrasound Contrast Agentsmentioning
confidence: 99%
“…For example, metastasis has been successfully diagnosed in axillary lymph nodes of patients with breast cancer using Sonazoid TM (28). Clinical trials are currently being performed, aiming to differentiate benign and malignant focal lesions in the breast (29). The present study shows a possible application for Sonazoid TM in CRC.…”
Section: A B C D E F G Hmentioning
confidence: 72%
“…Previous studies have reported that CEUS is useful for differentiating between benign and malignant breast lesions [1,2], evaluating the disease extent [3,4], and assessing the tumor response after neoadjuvant chemotherapy [5,6].…”
Section: Introductionmentioning
confidence: 99%